A Survey on Fault Identification System in OTN using Neural Network - Pardhi, Ravindra Laxman; Dhande, Sheetal S.; Govindwar, Ganesh D.; Pande, Ankita V. (International Journal of Membrane Science and Technology, 2023)
The diversity of information and services that are sent via optical networks is growing day by day, hence the survivability of optical networks has emerged as a significant research issue in recent years. The location of the fault in an optical transmission network (OTN) is very important when investigating the survivability of optical networks. The first step is to create network model with three channel, after which it is necessary to analyze common alarm data, as well as fault monitoring points and common fault sites. The fault location field of OTN incorporates the artificial neural network (ANN), which is used to identify whether or not a probable fault site is present. In this paper, we had done a review of earlier research work in this field and identified the research gap in the introduction of neural networks into the area of fault identification in optical transport networks.